The effects of concurrent endurance and resistance training on 2,000-m rowing ergometer times in collegiate male rowers - Gallagher, D.; DiPietro, L.; Visek, A. J.; Bancheri, J. M.; Miller, T. A. (The Journal of Strength and Conditioning Research, 2010)
The current study evaluated if high rep, low rep, or no weight training at all would be best suited for decreasing 2,000-m rowing ergometer times in male varsity rowers. Subjects (n = 18) were rowers from Grand Valley State University who were randomly and equally assigned to 1 of 3 groups: control (CON), high-load low repetitions (HLLR), and low-load high repetitions (LLHR). The weight training groups resistance trained and rowed twice a week, whereas the control group only rowed twice a week. Each group performed the training study workouts (weight training and rowing) along with their daily prescribed varsity practices. The subjects performed both pre and post 2,000-m ergometer tests on concept 2 indoor rowers to evaluate the effects of each training protocol. Paired t-tests revealed statistically significant decreases in 2,000-m times from pre to posttesting for all groups (p < 0.05), whereas a 1-way analysis of variance with repeated measures did not reveal a statistically significant difference (p < 0.96) between the 3 groups (deltaCON: -2.8%, deltaLLHR: -3.1%, and deltaHLLR: -3.5%). However, a trend existed in the hypothesized direction, as the HLLR illustrated the greatest decrease in mean rowing time (CON: 11 seconds, LLHR: 12 seconds, and HLLR: 15 seconds). Overall, the current study demonstrates that although weight training does not create a statistically significant short-term training effect on rowing performance, the profound decreases in 2,000-m times seen in this study may be of practical significance for the oarsman.